Farming Amidst Climate Change: Understanding, Perceived Effects and its Implications on the Livelihood of Farmers - Ibrahim, Aliah; Cabugatan, Nor-Aliah; Basari, Alipah; Paghasian, Romy (Golden Ratio of Social Science and Education, 2024)
This study used descriptive research methods to determine the understanding, perceived effects, and implications of climate change on the livelihood of the farmers in Barangay Sarip-Alawi, Balo-I, Lanao Del Norte. Interview Schedule was used as an instrument to obtain necessary information from the respondents of this study and the data were presented and analyzed using frequency, percentage and the weighted mean. As to level of understanding on climate change, the respondents held a very high level of understanding. The respondents strongly agreed that climate change has already occurred; that it is a global issue; it happened in their community; and it affects their livelihood. They strongly agreed that they perceived the effects of climate change on their farming activities. Moreover, the respondents strongly agreed that climate change can cause failures in their crop production, decrease of yield harvest, affect their farming schedule, affect the soil, and delay their harvesting activity. Thus, different strategies were used by the farmers to mitigate the effects of climate change on their farming and livelihood activities. Some of those mitigation and adaptation practices are by changing in cropping pattern and cropping technique calendar, diversifying of income-generating and other livelihood activities, and practicing multi-cropping.